Evaluation in terms of various parameters the selçuk university faculty of veterinary medicine graduates opinions - Aşkın Yaşar; Gökhan Aslım; Mehmet Emin Tekin; Mustafa Bahadır Çevrimli; Burak Mat; Mustafa Agah Tekindal (Eurasian Journal of Veterinary Sciences)
Aim: The Selçuk University Faculty of Veterinary Medicine started to education in 1982. The thousands of veterinarians graduated from Selçuk University Faculty of Veterinary Medicine since then. The present study aimed to identify the status of the veterinarians that graduated from Selçuk University Faculty of Veterinary Medicine, inquired into their areas of employment, constructed their profiles and presented their opinions according to various parameters. Materials and Methods: An Information Collection Form was drawn up via to implement and distributed to the respondents. SPSS 25 was used to evaluate the collected data. The median (IQR), percentage and frequency values of the variables were used. The categorical datas were analysed by Fishers Exact Test and Chi-Square Test. Results: It was found that 45.70% of the respondents had started career within one year, 64.40% had made an informed choice to enter the faculty, 86.50% were satisfied with their current job, and 73.10% had gained an understanding of professional and ethical responsibility during their education. Conclusion: Selçuk University Faculty of Veterinary Medicine has made significant contributions to the animal husbandry in almost all industry of the profession since its establishment. The present study can help raise the professional standards and pave the way for future studies required for this purpose if it is applied to the veterinarians that graduated from other veterinary faculties across the country.